WEAVING SOCIAL JUSTICE TEACHING IN CRITICAL LANGUAGE TEACHER EDUCATION / Tecendo o ensino de justiça social na Formação crítica de professores de línguas - Mattos, Andréa Machado de Almeida; Jucà, Leina Claudia Viana (Pensares em Revista, 2023)
This paper describes an experience of using critical literacy in teaching English to freshman students in the undergraduate English Language course at a large Brazilian university. The course was prepared with the aim of providing students with an experience in what has been called Critical Education in a Foreign Language (FERRAZ, 2010; 2015; FERRAZ; MATTOS, 2015; MATTOS, 2014; MATTOS; FERRAZ; MONTE MÓR, 2015; MONTE MÓR, 2009) and to help prepare them for their future as critical teachers. The article seeks to show how conceptions of critical teaching and critical literacy may be used as a starting point for teacher education and for the development of critical approaches to teaching English. In this sense, activities that were used during the course will be discussed, as well as some perceptions of the students, collected through discussions in the classroom. The proposal sought to encourage students to reflect on their roles in promoting social justice (HAWKINS, 2011; ZEICHNER, 2011) and responsible social transformation. Carrying out this experience taught us that simply discarding what the students – language learners and future teachers – recognize as language teachingmay confuse them and distance them from other possibilities of conceiving language teaching. It is important for students to have opportunities to perceive the existing differences between the objectives of traditional and critical language teaching, especially with regard to the type of citizen that these conceptions of language teaching help to educate and the different agency possibilities such citizens may have in the processes of social construction.